Adapting Biodegradable Oligo(Poly(Ethylene Glycol) Fumarate) Hydrogels for Pigment Epithelial Cell Encapsulation and Lens Regeneration - Zhang, Mimi W. (Mary Ann Liebert, Inc., 2010)
This study investigated the encapsulation of newt iris pigment epithelial cells (PECs), which have the ability to regenerate a lens by trans-differentiation in vivo, within a biodegradable hydrogel of oligo(poly(ethylene glycol) fumarate) crosslinked with poly(ethylene glycol)-diacrylate. Hydrogel beads of initial diameter of 1 mm were fabricated by a molding technique. The swelling ratio and degradation rate of the hydrogel beads decreased with increasing crosslinking ratios. Confocal microscopy confirmed the cytocompatibility of crosslinking hydrogel formulations as evidenced by the viability of an encapsulated model cell line within a crosslinked hydrogel bead. Hydrogel beads encapsulating iris PECs were also implanted into lentectomized newts in vivo; histological evaluation of explants after 30 days revealed a regenerated lens, thus demonstrating that the presence of degrading hydrogel did not adversely affect lens regeneration. The results of this study suggest the potential of a method for lens regeneration involving oligo(poly(ethylene glycol) fumarate) hydrogels for iris PEC encapsulation and transplantation.